2012
DOI: 10.4049/jimmunol.1200227
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of a Dengue Cross-Reactive Antibody Complexed with Envelope Domain III Reveals the Molecular Basis of Cross-Reactivity

Abstract: Dengue virus infections are still increasing at an alarming rate in tropical and subtropical countries underlying the need for a dengue vaccine. Although it is relatively easy to generate antibody responses to dengue virus, low avidity or low concentrations of antibody may enhance infection of Fc receptor-bearing cells with clinical impact, posing a challenge to vaccine production. In this paper we report the characterization of a monoclonal antibody, 2H12, which is cross-reactive to all four serotypes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 73 publications
5
83
0
1
Order By: Relevance
“…His317, the residue implicated in pH sensing 64, 65 , switches electrostatic polarity with respect to Thr315 ( Table 1). Both His317 and Thr315 are conserved in ZIKV/DENV1-4/JEV/WNV ( Figure 2), and are known epitopes 23, 43 . Another pair (Arg286-Arg288) with EPD-R are stereochemically equivalent in ZIKV/DENV1-4/JEV/WNV ( Figure 3), and lie on a putative GAG-binding domain preceding the DI/DIII linker 48, 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His317, the residue implicated in pH sensing 64, 65 , switches electrostatic polarity with respect to Thr315 ( Table 1). Both His317 and Thr315 are conserved in ZIKV/DENV1-4/JEV/WNV ( Figure 2), and are known epitopes 23, 43 . Another pair (Arg286-Arg288) with EPD-R are stereochemically equivalent in ZIKV/DENV1-4/JEV/WNV ( Figure 3), and lie on a putative GAG-binding domain preceding the DI/DIII linker 48, 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, a quantitative analysis of spatial and electrostatic perturbation in the pre 37 and post-fusion 12 DENV-2 E proteins was done using MEPP 38 . This revealed that highly perturbed residues are overwhelmingly conserved, and also epitopes of known neutralizing antibodies 23, 35, 3943 . Characterization of α -helices in E-proteins using techniques (PAGAL 44, 45 ) previously applied to the Ebola virus 46 , revealed that α 1 in ZIKV-E and DENV-E proteins is not conserved in the sequence space.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, anti-DIII antibodies have been shown to bind to epitopes that are not accessible in the known structures of the virus, suggesting that molecular rearrangements are required to expose them (54,55); on the other hand, antibody binding was shown to either alter the virus structure or trap the antigen in an already existing conformation (21).…”
Section: Discussionmentioning
confidence: 99%
“…2). Similarly, the epitopes of all other anti-DIII antibodies with a known structure are partially inaccessible on the virus surface (1A1D-2, 4E11, and 2H12) (20,54,55). Conformational changes causing different degrees of epitope exposure are likely important for the binding, specificity, and neutralization capacities of antibodies against the four different serotypes (20,27,58).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the observed variations in binding stoichiometry and epitope occupancy are typically attributed to relatively small conformational differences between symmetry-related epitopes that interfere with Ab binding or alter epitope accessibility. Although certainly plausible, such explanations seem at odds with evidence that 1) flaviviruses undergo ''breathing'' motions that confer considerable conformational heterogeneity (20), and 2) Ab binding can induce significant conformational changes, exposing previously buried epitopes (21). Furthermore, there are technical limits to the use of cryo-EM structures alone in understanding the mechanisms of antibody-based neutralization of flaviviruses.…”
Section: Introductionmentioning
confidence: 99%